1972
DOI: 10.1002/dev.420050309
|View full text |Cite
|
Sign up to set email alerts
|

Development of adult‐like open‐field behaviors in young retinal‐degenerate C3H mice

Abstract: Retinal degenerate C3H mice were tested in the open field under 2 illumination conditions before, during, and after the ages at which the early degenerate process occurs to determine whether the progressive destruction of the retina would result in the loss of brightness discrimination ability. From data collected on mice tested at 10, 14, 18, 22, 26, and 30 days of age, longitudinal and cross-sectional analyses were performed upon activity and and defecation scores to separate the effects of prior test experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Because C3H mice (20–100 days of age) have been shown to respond to brightness differences in the open field (Nagy & Misanin, 1970), their behavior may be indicative of some residual visual capacities beyond the early degeneration period. Moreover, C3H mice that were tested at various ages before, during, and after the onset of retinal degeneration were shown to be more active under low versus high illumination (Nagy & McKay, 1972). In this study, the authors concluded that although retinal degeneration in the second postnatal week renders the mice insensitive to certain types of visual cues, it does not produce total blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Because C3H mice (20–100 days of age) have been shown to respond to brightness differences in the open field (Nagy & Misanin, 1970), their behavior may be indicative of some residual visual capacities beyond the early degeneration period. Moreover, C3H mice that were tested at various ages before, during, and after the onset of retinal degeneration were shown to be more active under low versus high illumination (Nagy & McKay, 1972). In this study, the authors concluded that although retinal degeneration in the second postnatal week renders the mice insensitive to certain types of visual cues, it does not produce total blindness.…”
Section: Discussionmentioning
confidence: 99%
“…They may be measured manually, by video recording or by automated sampling making use of photo beams. The size of open field arenas used to study behavior of mice may reach 90 cm  90 cm, although most arenas range from 30 cm  30 cm to 60 cm  60 cm (Gill and Boyle, 2005;Henderson et al, 2004;Kafkafi et al, 2005;Leppanen and Ewalds-Kvist, 2005;Nagy and McKay, 1972;Singer et al, 2005;Trullas and Skolnick, 1993). In a smaller open field arena the measurement of locomotor activity is more reliable, because emotional factors influencing locomotor activity are supposed to be reduced.…”
Section: The Test System Motility Boxmentioning
confidence: 98%
“…The behavior in the open field is influenced by visual (Nagy and McKay, 1972) and tactile cues (Meyer and Meyer, 1992;Luhmann et al, 2005;Treit and Fundytus, 1988). The C3H/HeN mice used in the Fig.…”
Section: The Test System Motility Boxmentioning
confidence: 99%